Effects of air pollution control measures on air quality improvement in Guangzhou, China. (15th August 2019) - Yu, Meifang; Zhu, Yun; Lin, Che-Jen; Wang, Shuxiao; Xing, Jia; Jang, Carey; Huang, Jizhang; Huang, Jinying; Jin, Jiangbo; Yu, Lian
Abstract: The ambient air quality of Guangzhou in 2016 has significantly improved since Guangzhou and its surrounding cities implemented a series of air pollution control measures from 2014 to 2016. This study not only estimated the effects of meteorology and emission control measures on air quality improvement in Guangzhou but also assessed the contributions of emissions reduction from various sources through the combination of observation data and simulation results from Weather Research and Forecasting - Community Multiscale Air Quality (WRF-CMAQ) modeling system. Results showed that the favorable meteorological conditions in 2016 alleviated the air pollution. Compared to change in meteorology, implementing emission control measures in Guangzhou and surrounding cities was more beneficial for air quality improvement, and it could reduce the concentrations of SO2, NO2, PM2.5, PM10, and O3 by 9.7  μ g m −3 (48.4%), 9.2  μ g m −3 (17.7%), 7.7  μ g m −3 (14.6%), 9.7  μ g m −3 (13.4%), and 12.0  μ g m −3 (7.7%), respectively. Furthermore, emission control measures that implemented in Guangzhou contributed most to the concentration reduction of SO2, NO2, PM2.5, and PM10 (46.0% for SO2, 15.2% for NO2, 9.4% for PM2.5, and 9.1% for PM10 ), and it increased O3 concentration by 2.4%. With respect to the individual contributions of source emissions reduction, power sector emissions reduction showed the greatest contribution in reducing the concentrations of SO2, NO2, PM2.5, and PM10 due to the implementation of Ultra-Clean control technology. As for O3 mitigation, VOCs product-related source emissions reduction was most effective, and followed by transportation source emissions reduction, while the reductions of power sector, industrial boiler, and industrial process source might not be as effective. Our findings provide scientific advice for the Guangzhou government to formulate air pollution prevention and control policies in the future. Graphical abstract: Image 1 Highlights: The first study on assess the contribution of source emissions reduction in Guangzhou. Meteorology in 2016 was in favor of air pollution mitigation compared to that in 2013. The control measures of Guangzhou played a dominant role in air quality improvement. Power sector emissions control was the largest contributor to air pollution abatement.